Exploring magnetic field impacts on electromagnetically induced transparency: Decoherence and nonlinear effects in rubidium vapor - Jin Wang; Amy Krause (AIP Advances)
This study explores electromagnetically induced transparency (EIT) with a focus on the influence of external magnetic fields, examining effects such as decoherence, Faraday rotation, coherence decay, and signal detuning. This model extends previous analyses by introducing dimensions of coherence decay across atomic densities, nonlinear Faraday rotation dependencies, and transmission responses to detuning. The findings show strong agreement with experimental observations in rubidium vapor systems and provide new insights relevant to applications in quantum memory, magnetic sensing, and optical modulation. Additionally, an analogy to classical RLC circuits is employed to offer an intuitive framework for understanding decoherence’s impact on EIT.